Techno-economic analysis of green methanol plant with optimal design of renewable hydrogen production: A case study in China. (26th January 2022) - Gu, Yu; Wang, Danfeng; Chen, Qianqian; Tang, Zhiyong
Abstract: Using renewable energy to convert carbon dioxide (CO2 ) into methanol has gained extensive attention. This study focuses on a green methanol plant which contains both upstream green hydrogen-electricity production system and downstream CO2 -based methanol synthesis. Three configurations were designed and optimized for the upstream off-grid hydrogen-electricity production system to obtain the minimum hydrogen cost. The optimization was conducted based on hourly meteorological data at Ordos, Inner Mongolia, China, as well as the hydrogen and electricity consumption by the downstream CO2 hydrogenation unit. On top of that, an integrative techno-economic analysis was conducted on the entire green methanol plant. Furthermore, the effect of key parameters and carbon tax on the economy of such green methanol plant was also explored. The results indicate that (1) for Ordos, the green methanol plant adopting photovoltaic-wind powered hydrogen production system (PV-Wind-H2 -methanol) with oxygen selling has the lowest levelized cost of methanol, of which the upstream green hydrogen-electricity production system occupies 77%; (2) byproduct oxygen selling and CO2 source option has a significant effect on the methanol cost; (3) for PV-Wind-H2 -methanol system, wind turbine cost is the most influential economic factor. To make the methanol cost of the PV-Wind-H2 -methanol system to be lower than the conventional methanol cost, the cost of wind turbines and PV needs to be reduced by at least 50% at the same time; (4) if considering carbon tax, the PV-Wind-H2 -methanol system will have potential to compete with conventional methanol plant. Highlights: Methanol production from CO2 and green H2 based on local weather resources is optimized. PV-Wind driven system has the lowest H2 cost and methanol cost. Oxygen selling option and CO2 capture source obviously affect the methanol cost. PV-Wind-H2 -methanol system can compete with traditional plant considering carbon tax.